On MMSE real-time antenna array processing using fourth-order statistics in the US cellular TDMA system. - Martone, M.
The antenna array processing problem in the reverse link of the current US digital cellular communication system is studied and higher-than-second-order-statistics (HOS) baseband processing is proposed as a possible candidate solution. The remarkable difference of our approach as compared to other existing similar techniques is the idea of the minimization of the mean squared error using fourth-order cumulants alone and nonblind criteria. A recursive Jacobi total least squares algorithm is used in the adaptive implementation to mitigate the effects of high error variance in the estimates of the cumulants based on sample statistics. The method is shown to be very effective in a fast fading environment with multiple cochannel interferers
Keywords: MMSE; TDMA; USA; Adaptive implementation; Baseband processing; Deconvolution; Digital cellular communication system; Discrete-time model; Fast fading environment; Fourth-order cumulants; Fourth-order statistics; High error variance; Higher-than-second-order-statistics.; Mean square error minimization; Multiple cochannel interferers; Nonblind criteria; Propagation channel model; Real-time antenna array processing; Recursive Jacobi total least squares algorithm; Sample statistics